1984
DOI: 10.1139/v84-024
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of trisubstituted cyclopentadienes and their reactivity in the intramolecular Diels–Alder reaction

Abstract: The intramolecular Diels–Alder reactivity of several trisubstituted cyclopentadienes is described and a general method for their preparation reported. In general, sidechain keto-ester functionality has an adverse effect on these internal cycloadditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…This has been used to advantage by Breitholle and Fallis in the cyclization of 283 for the total synthesis of cedrene and cedrol (186). Although this sigmatropic rearrangement leading to 280 foiled an early approach to longifolene (15), a similar ring system from 284 is currently being investigated as a route to the sesterterpene gascardic acid (187).…”
Section: Bridged Ring Adducts (Cyclic Dienes)mentioning
confidence: 99%
“…This has been used to advantage by Breitholle and Fallis in the cyclization of 283 for the total synthesis of cedrene and cedrol (186). Although this sigmatropic rearrangement leading to 280 foiled an early approach to longifolene (15), a similar ring system from 284 is currently being investigated as a route to the sesterterpene gascardic acid (187).…”
Section: Bridged Ring Adducts (Cyclic Dienes)mentioning
confidence: 99%
“…In spite of considerable recent attention, the subtle substituent effects governing intramolecular Diels-Alder reactions are still imperfectly understood (10,11,19,(24)(25)(26)(27)(28)(29)(30). The key cycloaddition steps in the syntheses above were dia~tereos~ecific and were clearly dominated by the presence of the benzyl ether substituent and its orientation.…”
Section: Discussionmentioning
confidence: 99%
“…cyclopentadienes A-C, the cycloadditions will proceed to give the fused ring product D rather than the isomeric bridged ring or Bredt olefin adducts E and F (7,8,12). Our earlier investigations revealed that the cycloheptane ring could not be generated directly and that ultimately a ring expansion would be required (7).…”
Section: Can I Chem \mentioning
confidence: 99%
“…Our earlier investigations revealed that the cycloheptane ring could not be generated directly and that ultimately a ring expansion would be required (7). In addition, it was established that carrying the dimethylhexenyl substituent caused difficulties, due to competing ene reactions during the cycloaddition step.…”
Section: Can I Chem \mentioning
confidence: 99%
See 1 more Smart Citation